2017
DOI: 10.1007/s40692-017-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

Design and recognition of multimodal texts: selection of digital tools and modes on the basis of social and material premises?

Abstract: In recent years, national access to and use of digital tools has increased rapidly in Swedish schools. This article draws upon experiences from a qualitative study conducted in Sweden. This study explored student's use of multimodal texts and how students and their teachers perceive and recognize the multimodal texts produced in project assignments. The empirical material was gathered from six different project assignments at two different secondary schools in Sweden. The data consisted of students' multimodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Type B studies’ therefore call for designing new forms of criteria, rubrics or metalanguage that better scaffold and support multimodal composition and learning from a multiliteracies lens. As another example, Svärdemo-Åberg and Åkerfeldt (2017) propose and illustrate a multimodal perspective offering teachers and students a metalanguage for visual, auditory and linguistic (written) design that supports formative and summative assessment of multimodal compositions. Specifically, this multimodal design framework includes examining the digital tools and modes students use (and their combinations), the form student compositions take (structure, sequencing, thematic orientation, modal affordances), and how the overall ensemble relates to specific genres.…”
Section: Resultsmentioning
confidence: 99%
“…Type B studies’ therefore call for designing new forms of criteria, rubrics or metalanguage that better scaffold and support multimodal composition and learning from a multiliteracies lens. As another example, Svärdemo-Åberg and Åkerfeldt (2017) propose and illustrate a multimodal perspective offering teachers and students a metalanguage for visual, auditory and linguistic (written) design that supports formative and summative assessment of multimodal compositions. Specifically, this multimodal design framework includes examining the digital tools and modes students use (and their combinations), the form student compositions take (structure, sequencing, thematic orientation, modal affordances), and how the overall ensemble relates to specific genres.…”
Section: Resultsmentioning
confidence: 99%
“…Smith's (2014) review on L2 education and multimodal approaches to writing showed that a multimodal approach to teaching in L2 was beneficial to student learning in a number of areas, including academic writing, when combined with explicit instruction. Research on L1 supports the benefits of multimodality for developing writing and reading both in early L1 education (Mackenzie and Veresov, 2013;Sofkova Hashemi, 2017) and throughout the school years (Oldham, 2005;Pantaleo, 2012;Svärdemo Åberg and Åkerfeldt, 2017). There are also studies which report on how a multimodal approach is difficult to enact in the classroom due to issues related to school traditions, teachers' competence, the challenges of power relations in the classroom and even the students' resistance (Aagard and Silseth, 2017; Cederlund and Sofkova Hashemi, 2018;Gilje, 2010;Godhe, 2014;Olin-Scheller, 2006).…”
Section: Theoretical Framework -A Multimodal Socio-semiotic Approachmentioning
confidence: 99%
“…This expansion of print towards digital, multimodal representations enables teachers to present their material in new ways and, similarly, students to learn using diverse modes and media and demonstrate their knowledge producing multimodal representations (e.g. Sofkova Hashemi, 2017;Svärdemo & Åkerfeldt, 2017;Andersen & Munksby, 2018).…”
Section: Contemporary Teaching and Learning Landscapementioning
confidence: 99%